Family Self Stigma at People with Mental Disorder - Efri Widianti; Nur Hardini Rahmatika; Nita Fitria (Jurnal Ilmu Keperawatan Jiwa, 2020)
Self-stigma mostly occurs in individuals with mental illness or in their family. Self-stigma has the impact on decreasing family self-esteem and disruption of family member’s recovery process. Some of the family seceded from social environment and health services. The aim of the study was to identify family’s self-stigma with mental illness member in the working area of Puskesmas Jatinangor. This study used a descriptive quantitative method with the cross-sectional approach. Consecutive sampling was used to obtain 32 samples. This study used The Family Experience Interview Schedule (FEIS) Scale – Section L (Stigma) with the value of validity 0,71-0,84 and value of Cronbach alpha 0,851. This instrument has score ranged from 0 – 15. A higher score signifies higher self-stigma perceived by family.  The data obtained in this study were analyzed using univariate analysis.  The results showed the score of self-stigma within the range of 0 – 9 from the maximum total score 15 with the mean of 3,31 and SD 2,402. The item which was dominantly perceived by the family was the anxiety which appears when the condition of their mentally ill family member was found by others. Based on the results of the study, family felt 3 items out of 15 items on the instrument. A psychoeducation program for reducing anxiety in the family has to be encouraged in primary health care, especially in the nursing program.